Menorismo estrutural e o direito: elementos para uma hermenêutica constitucional insurgente e antimenorista - Schweikert, Peter Gabriel Molinari (2022)
This dissertation aims to critically demonstrate the existence of plural manifestations of the minorism’s phenomenon in the Brazilian society and present elements for the construction of a hermeneutic proposal that takes them into account and contributes to the process of political struggle for the emancipation of children and adolescents. Given its multidisciplinary character, the method of historical and dialectical materialism was chosen as an analytical proposal for understanding the social relations in which boys and girls figure as participants. Such understanding, in view of the totality of social relations, permeated the investigative immersion in three dimensions: historical, legal and ideological. Structural studies in the sociology of childhood, the Unitary Theory of Social Relations and studies on Insurgent Law were also presented as epistemological supports, which provided the theoretical basis for the identification of the three forms of manifestation of Minorism in society ( individualist, institutional and structural). Then, we sought to rescue, in the field of legal hermeneutics, proposals permeable to the findings presented in the first part of the work, choosing Konrad Hesse's hermeneutic-concretizing proposal as a starting point. Once the interpretative theory of Hesse was approximated to the studies of Insurgent Law and the conclusions gathered on the dimensions of Minorism, the result was the identification of elements for the construction of a proposal of insurgent and antiMenorist hermeneutics. Finally, we tried to test the proposal in different practical situations, indicating possible alternative solutions for the analyzed cases